German S3 guidelines: anal abscess and fistula (second revised version) - Ommer, Andreas; Herold, Alexander; Post, Stefan (Langenbeck's archives of surgery, 2017)
The incidence of anal abscess and fistula is relatively high, and the condition is most common in young men. This is a revised version of the German S3 guidelines first published in 2011. It is based on a systematic review of pertinent literature.